Regulation of Tomato Fruit Polygalacturonase mRNA Accumulation by Ethylene: A Re-Examination - Sitrit, Yaron (American Society of Plant Physiologists, 1998)
Polygalacturonase (PG) is the major enzyme responsible for pectin disassembly in ripening fruit. Despite extensive research on the factors regulating PG gene expression in fruit, there is conflicting evidence regarding the role of ethylene in mediating its expression. Transgenic tomato (Lycopersicon esculentum) fruits in which endogenous ethylene production was suppressed by the expression of an antisense 1-aminocyclopropane-1-carboxylic acid (ACC) synthase gene were used to re-examine the role of ethylene in regulating the accumulation of PG mRNA, enzyme activity, and protein during fruit ripening. Treatment of transgenic antisense ACC synthase mature green fruit with ethylene at concentrations as low as 0.1 to 1 μL/L for 24 h induced PG mRNA accumulation, and this accumulation was higher at concentrations of ethylene up to 100 μL/L. Neither PG enzyme activity nor PG protein accumulated during this 24-h period of ethylene treatment, indicating that translation lags at least 24 h behind the accumulation of PG mRNA, even at high ethylene concentrations. When examined at concentrations of 10 μL/L, PG mRNA accumulated within 6 h of ethylene treatment, indicating that the PG gene responds rapidly to ethylene. Treatment of transgenic tomato fruit with a low level of ethylene (0.1 μL/L) for up to 6 d induced levels of PG mRNA, enzyme activity, and protein after 6 d, which were comparable to levels observed in ripening wild-type fruit. A similar level of internal ethylene (0.15 μL/L) was measured in transgenic antisense ACC synthase fruit that were held for 28 d after harvest. In these fruit PG mRNA, enzyme activity, and protein were detected. Collectively, these results suggest that PG mRNA accumulation is ethylene regulated, and that the low threshold levels of ethylene required to promote PG mRNA accumulation may be exceeded, even in transgenic antisense ACC synthase tomato fruit.